History and Culture of Minangkabau in Educational Perspective: Integrating Traditional Values for Character Development - Aldi, Muhammad; Khairanis, Retisfa (Universitas Muhammadiyah Surakarta, 2025)
This study aims to identify traditional Minangkabau cultural values relevant to character education and their contextual integration within contemporary educational practices, both formal and non-formal. Rooted in a rich cultural and philosophical tradition, the Minangkabau community upholds values such as deliberation (musyawarah), mutual cooperation (gotong royong), and respect for elders—principles that align closely with the objectives of character formation. Employing a qualitative research design with a historical-cultural approach, data were collected through literature review, in-depth interviews with traditional leaders and educators, and participatory observations in Minangkabau communities. Thematic analysis was used to interpret the data and identify key cultural elements with educational relevance. Findings reveal that core Minangkabau principles, notably Adat Basandi Syarak, Syarak Basandi Kitabullah, and the traditional surau-based learning model, contribute significantly to fostering ethical, social, and spiritual dimensions of character. However, the research also highlights the tension between traditional value systems and the demands of standardized modern education, which often marginalizes local wisdom. The study underscores the importance of developing culturally responsive curricula that integrate indigenous values into character education frameworks. This research contributes to broader educational discourse by offering practical insights for educators and policymakers seeking to enrich national education systems through the integration of local cultural heritage. It advocates for a sustainable approach to character education that balances cultural identity with educational innovation.